Infant, child and adolescent nutrition : a practical handbook - More, Judy. (Boca Raton : CRC Press, 2013)
This evidence-based, practical guide provides an introduction to the theory behind child nutrition with practical advice on how to put that theory into practice, including case studies, key points and activities to help readers learn. Divided into three sections, the chapters cover pre-natal nutrition and nutrition throughout childhood from pre-term babies to adolescents up to the age of 18. Section 1: Introduction to the growth, nutrients and food groups. Section 2: Providing a balanced eating pattern for each age group, chapters include expected growth patterns, development affecting eating and drinking skills, as well as common problems such as reflux in babies, fussy eaters in the toddler years and eating disorders and pregnancy in the teenage years. Section 3: Common problems/disorders that can occur at any stage throughout childhood such as obesity, diabetes and food intolerances. Chapters will also cover nutritional support in the community, reflecting the increasing numbers of chronically sick children who are now managed in the primary care setting --
Includes bibliographical references and index.
Keywords: Children -- Nutrition; Infants -- Nutrition; Teenagers -- Nutrition; Infant Nutritional Physiological Phenomena; Adolescent Nutritional Physiological Phenomena; Adolescent; Child Nutritional Physiological Phenomena; Child; Health Promotion; Infant